Contribution of Self-Efficacy and Self-Esteem to Subjective Well-Being - Wardoyo, Tulus; Awalya, Awalya; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2021)
In learning process, students are expected to have high subjective well-being. Unfortunately, the fact shows that many students suffer from low self-efficacy and self-esteem, which affects their subjective well-being. The present study aimed to analyze the the effect of self-efficacy and self-esteem on students’ subjective well-being. This study involved 350 students (50.7 % Male students and 44.3% female students) who were recruited using cluster random sampling technique. The data were collected using General Self-Efficacy Scale (GSE), The Short Form of Coopersmith SelfEsteem Inventory (SF-CSEI) dan Satisfaction With Life Scale (SWLS). Using SPSS, multiple linear regression analysis technique was applied. Self-efficacy and self-esteem were found to predict students’ subjective well-being. They simultaneously accounted for the variance of subjective well-being by 24.2% ( =0.242). Following the result, school counselors are recommended to develop students’ self-efficacy and self-esteem in order to enhance their subjective well-being